Implementation of the MDLC Method for Optimizing Smart Board Functionality in a Sundanese Alphabet Educational Game Application - Miftah Nurjamil; Yiyi Supendi; Irwin Supriadi (Jurnal Impresi Indonesia, 2026)
Sundanese script learning in elementary schools still faces obstacles in terms of student involvement and understanding due to the use of conventional methods that tend to be passive. This research aims to develop a Smart Board-based learning game application using the Multimedia Development Life Cycle (MDLC) method and evaluate its effectiveness in improving the quality of learning. The developed app integrates interactive multimedia, gamification, and touch-based interactions to create a more active and engaging learning experience. System testing is carried out using the black box testing method to ensure that all application functions run properly. Evaluations were conducted on 50 elementary school students using a Likert scale questionnaire with indicators of understanding, motivation, and interaction. The results showed that the application obtained an average score of 4.72 which was included in the category of very effective. The motivation aspect has the highest score, followed by interaction and understanding, which shows that the application of gamification and Smart Boards is able to significantly increase student engagement and understanding. Thus, the app can be an effective alternative to interactive learning media as well as support the preservation of local culture through a technology-based approach.